Manajemen Usaha Masjid Ittihad Legenda Wisata Cibubur dalam Mewujudkan Kemandirian Ekonomi - Nurjanah Nurjanah; Febrianto, Adit; Sucipto, Arief Syarifuddin; Hartono Hartono; Waluyo, Agus (Lembaga Pengembangan Kinerja Dosen, 2026)
The mosque, as a socio-religious institution, plays a strategic role in promoting community welfare not only in spiritual aspects but also in economic development. This study aims to analyze the implementation of business management functions at Masjid Ittihad Legenda Wisata Cibubur in realizing the economic independence of its congregation. The research focuses on four key management functions proposed by George R. Terry—planning, organizing, actuating, and controlling. A qualitative descriptive approach with a case study design was applied, utilizing in-depth interviews, participatory observation, and documentation involving mosque administrators and congregants. The results reveal that the management of Masjid Ittihad applies Islamic-based management principles such as trustworthiness (amanah), justice (adl), and consultation (syura) in running its economic units, including a cooperative and community bazaar. The key supporting factors are the active participation of congregants, strong social cohesion, and visionary leadership from the mosque’s management. However, challenges remain, including limited capital, lack of entrepreneurship training, and suboptimal financial oversight. Effective business management has been shown to enhance congregational economic participation and foster collective awareness of the importance of financial self-reliance within the mosque community. Hence, mosque-based business management can serve as a sustainable model for Islamic economic empowerment when professionally and ethically administered.